The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/pse.58
|View full text |Cite
|
Sign up to set email alerts
|

Intersections in steel shell structures

Abstract: Cylinders, cones, spheres and tori are some of the common basic shell elements. Steel shell structures such as silos, tanks, pressure vessels, offshore platforms, chimneys and tubular towers generally consist of two or more of these basic shell elements. Axisymmetric intersections featuring meridional slope mismatches between the connected elements are common features in steel shell structures. High bending and circumferential membrane stresses are developed in these intersections, and their buckling and colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…For applications to terrestrial structures there are specialized reviews, e.g. on metal silos [170], shell intersections [171] and on pressure vessel components [172].…”
Section: Discussionmentioning
confidence: 99%
“…For applications to terrestrial structures there are specialized reviews, e.g. on metal silos [170], shell intersections [171] and on pressure vessel components [172].…”
Section: Discussionmentioning
confidence: 99%
“…Teng [33] presented a survey of research, most conducted in the Hong-Kong University, on the stress, stability and strength of silos transition junctions as axisymmetric steel shell intersections. Particular attention was paid to intersections formed from cylindrical and conical segments as these were more common and had been more extensively researched.…”
Section: Books and Reviewsmentioning
confidence: 99%
“…A more recent review of research on steel shell junctions including steel silo transition junctions can be found in Ref. [10].…”
Section: Introductionmentioning
confidence: 99%